Computational and experimental investigation of refractory high entropy alloy Mo15Nb20Re15Ta30W20 - Uttam Bhandari; Congyan Zhang; Congyuan Zeng; Shengmin Guo; Shizhong Yang (Journal of Materials Research and Technology, 2020)
In this study, refractory high entropy alloys (RHEAs) Mo20Nb20Re20Ta20W20, Mo15Nb20Re15Ta30W20, and Mo15Nb20Re10Ta35W20 were studied by applying the first-principles density functional theory (DFT) method. The DFT calculation was based on a large unit cell model of 100-atom supercell, with randomly distributed five element atoms. The mechanical properties of all three RHEAs were calculated and compared. Comparing with the other two RHEAs, Mo15Nb20Re15Ta30W20 possesses balanced mechanical properties with an optimized concentration of expensive Re element. We combined the DFT calculations of a supercell with Debye–Grüneisen theory to investigate the thermal properties of the two RHEAs Mo20Nb20Re20Ta20W20 and Mo15Nb20Re15Ta30W20. Mo15Nb20Re15Ta30W20 was selected for further experimental exploration and the computational results were compared. The experimental study shows the existence of a single BCC structure of Mo15Nb20Re15Ta30W20. The crystal structure, density, lattice parameter, and hardness predicted computationally are consistent with the experiment data.